(untitled) (International journal of medical sciences, 2026)
Odontoid phlegmons are severe purulent-inflammatory diseases of the maxillofacial region that require dental students to have well-developed clinical thinking and practical surgical skills. The aim of the study was to evaluate the effectiveness of simulation-based training using clinical scenarios and a biological model. A comparative analysis of knowledge, clinical thinking, and practical skills before and after training showed a statistically significant improvement in training, increased confidence in performing surgical procedures, and increased motivation to learn. The results of the study demonstrated a statistically significant improvement in the professional training of students, increased confidence in performing surgical procedures, and increased motivation to learn, confirming the high pedagogical effectiveness of the method.